Colloidal organic carbon and trace elements in peat porewaters across a permafrost gradient in Western Siberia - Raudina, Tatiana V.; Loiko, Sergey V.; Kuzmina, Daria M.; Shirokova, Liudmila S.; Kulizhsky, Sergey P.; Golovatskaya, Evgeniya A.; Pokrovsky, Oleg S. (Geoderma, 2021)
The majority of organic carbon (OC), nutrients, and dissolved trace elements in soil porewaters are present in the form of colloids which determine element transport, bioavailability, and overall impact on ecosystems. Climate warming and permafrost thaw in high latitudes will primarily affect the soil liquid phase thereby modifying delivery of colloids to the hydrological network and their role in C transport and emission. Here we studied colloids in peat porewaters across a natural gradient of sporadic, isolated, discontinuous and continuous permafrost zone in the Western Siberian Lowland (WSL), the largest peatland in the world. The depth of sampling and the microrelief (mounds and hollows) had a generally weak impact on the proportion of colloidal forms (3kDa 0.45 μm) of OC, major (Fe, Al, P, alkali and alkaline-earth metals) and trace elements (TE) including micronutrients (Zn, Mn, Ni, Co, Cu), toxicants (Sb, As, Cd, Pb) and geochemical tracers (trivalent and tetravalent cations). Considering all micro-landscapes together, there was no sizable change in the proportion of colloidal fraction of OC, Fe, Al, P, micronutrients and toxicants across the permafrost zones. The majority of colloidal forms of all elements of these groups were represented by a size fraction between 3 and 30 kDa and were essentially Fe-Al-organic compounds with an average Fe:Al:OC molar ratio of 1.9:1:308. Overall, the degree of impact from environmental factors on OC and metal distribution among various colloidal fractions can be classified as depth ≤ permafrost type < microlandscape. Applying a substitution “space for time scenario” for the climate warming and permafrost thaw in Western Siberia, we do not expect sizable changes in C and element colloidal status during active layer thickness increase and permafrost boundary shift northward. Future studies of colloids in peat ice (below the active layer) are needed to assess possible changes in delivery of C and metals from soil to rivers and onward into the Arctic Ocean under massive ...